Karakteristik Klinis Pasien Low Vision Anak di Pusat Mata Nasional Rumah Sakit Mata Cicendo pada Tahun 2021 - Rahma, Amelia Nafisah; Sirait, Susanti Natalya; Gustianty, Elsa (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2024)
Background: In Indonesia, low vision poses a significant public health issue, especially to children, which could lead to challenges in performing daily activities and diminished quality of life. This study aimed to describe the clinical characteristics of pediatric patients with low vision diagnosis in Cicendo Eye Hospital Bandung. Methods: All medical records of low vision patients aged 0-17 at Cicendo Eye Hospital Bandung during 2021 were reviewed. Data collected were patient’s age, gender, area of origin, main diagnosis of low vision cause, visual acuity, and low vision aids and/or rehabilitation given. Result: From 172 medical records reviewed, majority of patients were male (54.07%). The age group of 10-17 years had the largest proportion (38.95%). Majority of patients lived in Bandung and its surroundings (51.16%). A total of 52.33% patient experienced moderate visual impairment and 34.3% experienced severe visual impairment. Most common anatomical cause of low vision was posterior segment abnormality, with Retinopathy of Prematurity as the main cause (13.37%), followed by retinal dystrophy (12.79%). Low vision aid that was most commonly prescribed were glasses, followed by telescope. Conclusion: Pediatric low vision patients at Cicendo Eye Hospital were mostly male, in the age group of 10-17 years, and lived in Bandung and its surrounding. The most common classification of low vision cause was posterior segment abnormality, with Retinopathy of Prematurity as the main diagnosis. The most widely used low vision aids were glasses. Keyword: Characteristic, low vision, visual impairment